Development of Bio-Rational Based Management Packages Against Root Knot (Meloidogyne Incognita) Of Bottle Gourd (Bangladesh Journal of Agricultural Research, 2023)
The efficacy of Tricho-compost alone and combination of lower dose of Furadan 5G with Tricho-compost, poultry refuse, neem oil cake and saw dust burning against root-knot nematode (Meloidogyne incognita) of bottle gourd was studied in the field laboratory of Plant Pathology Division of Bangladesh Agricultural Research Institute (BARI) during 2017 through 2019 cropping seasons. All the treatments gave appreciable reduction of gall development on roots and enhanced shoot and root growth as well as fruit yield of bottle gourd. Integration of Furadan 5G with Trichoderma based bio-fungicides. Trichocomposts, neem oil cake, and poultry refuse were the effective treatments in reducing root-knot severity and increasing plant growth and fruit yield of bottle gourd.Bangladesh J. Agril. Res. 46(4): 373-383, December 2021